BEHAVIORAL FINANCE PSYCHOLOGY: A REVIEW PAPER - Fogaat, Mohit; Sharma, Sangeetha; Meena, Dr. Rajendra Prasad (The journal of contemporary issues in business and government, 2022)
This investigation will seek for and evaluate research publications on the subject of behavioural finance that have been published in a methodical manner in order to accomplish its goals. A fresh researcher who may be interested in the topic of behavioural finance may benefit from the findings of this study. This study includes 55 articles from the Journal of Behavioral Finance, 125 research articles linked to the field of behavioural finance, and about 300 authors' contributions to the field. In our research papers, we provide a number of research articles on behavioural finance that are on the cutting edge of the subject and are helping to establish behavioural finance as an important area of study. We did not include any extremely old behavioural finance research papers in our analysis since they were considered too old. It does not imply that previous researchers did not make significant contributions to the area of behavioural finance, but rather that the motivations for what has occurred in recent years are more relevant to new researchers than very old studies in the field of behavioural finance. In our study, we gathered data from 125 research articles from Elsevier and emerald publications, among other open access platforms. These databases served as a tool for analyzing the research articles in question.